2014
DOI: 10.3109/14767058.2014.995083
|View full text |Cite|
|
Sign up to set email alerts
|

Personalized third-trimester fetal growth evaluation: comparisons of individualized growth assessment, percentile line and conditional probability methods

Abstract: Objective To compare third trimester size trajectory prediction errors for three individualized fetal growth assessment methods. Methods This study utilized longitudinal measurements of 9 directly measured size parameters in 118 fetuses with normal neonatal growth outcomes. Expected Value [EV] function coefficients and variance components were obtained using two-level random coefficient modeling. Growth models [IGA] or EV coefficients and variance components [PLM, CPM] were used to calculate predicted values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These velocity values were then compared to reference ranges previously calculated in a cohort of fetuses with normal growth outcomes. 28 Participants (n = 0) delivering before their 34- to 36-week scan were excluded. Expected and observed measurements at 34-36 weeks were compared as follows: percent deviation = 100 × (observed-predicted)/predicted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These velocity values were then compared to reference ranges previously calculated in a cohort of fetuses with normal growth outcomes. 28 Participants (n = 0) delivering before their 34- to 36-week scan were excluded. Expected and observed measurements at 34-36 weeks were compared as follows: percent deviation = 100 × (observed-predicted)/predicted.…”
Section: Methodsmentioning
confidence: 99%
“… 23 , 24 , 25 , 26 Second-trimester TVol measurements can also be used to generate Rossavik models for predicting TVol and EFW growth trajectories during the third trimester. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of L-IUGR is more difficult, due to the large variability of fetal parameters on growth charts in the third trimester [4,31]. L-IUGR can be suspected when the individual growth curve slows down or even become flat [32] (fig 4).…”
Section: L-iugrmentioning
confidence: 99%
“…There is also the potential for using 3D sonography to measure fetal volumes at earlier gestations to enable calculation of ideal third‐trimester growth trajectories . This particular use of 3D sonography, using the fractional thigh volume and Rossavik growth models in individualized growth assessment, has been prospectively evaluated in a normal‐pregnancy population and showed good prediction of third‐trimester growth from second‐trimester measurements . Other studies examining placental volumes in the first‐trimester have demonstrated that 3D methods are superior when compared to 2D sonography with regard to the accuracy of volume measurements .…”
mentioning
confidence: 99%
“…5 This particular use of 3D sonography, using the fractional thigh volume and Rossavik growth models in individualized growth assessment, has been prospectively evaluated in a normal-pregnancy population and showed good prediction of thirdtrimester growth from second-trimester measurements. 6,7 Other studies examining placental volumes in the first-trimester have demonstrated that 3D methods are superior when compared to 2D sonography with regard to the accuracy of volume measurements. 8 Placental volumes have been evaluated in an attempt to enable earlier detection of those pregnancies resulting in small-for-gestational-age neonates, early-onset intrauterine growth restriction, and preeclampsia.…”
mentioning
confidence: 99%